Agromonas: a rapid disease assay for Pseudomonas syringae growth in agroinfiltrated leaves. (12th January 2021) - Buscaill, Pierre; Sanguankiattichai, Nattapong; Lee, Yoon Joo; Kourelis, Jiorgos; Preston, Gail; van der Hoorn, Renier A. L.
Summary: The lengthy process to generate transformed plants is a limitation in current research on the interactions of the model plant pathogen Pseudomonas syringae with plant hosts. Here we present an easy method called agromonas, where we quantify P. syringae growth in agroinfiltrated leaves of Nicotiana benthamiana using a cocktail of antibiotics to select P. syringae on plates. As a proof of concept, we demonstrate that transient expression of PAMP receptors reduces bacterial growth, and that transient depletion of a host immune gene and transient expression of a type‐III effector increase P. syringae growth in agromonas assays. We show that we can rapidly achieve structure−function analysis of immune components and test the function of immune hydrolases. The agromonas method is easy, fast and robust for routine disease assays with various Pseudomonas strains without transforming plants or bacteria. The agromonas assay offers a reliable approach for further comprehensive analysis of plant immunity. Significance Statement: This technical advance introduces a robust and reliable disease assay to monitor bacterial growth of Pseudomonas syringae in agroinfiltrated tissues using an antibiotics cocktail to select against Agrobacterium tumefaciens .